The Emotional Status, Attitudes in Decision-Making Process, and Their Impact on Surgical Choices in Korean Breast Cancer Patients - Jeon, Sook Young (J Oncol, 2021)
PURPOSE: We examined the incidence of emotional distress in women with newly diagnosed breast cancer to determine whether the degree of emotional distress affected their choice of breast-conserving surgery (BCS) or mastectomy and evaluated how the patient's preferred role in decision-making influenced her choice of surgical method. METHODS: This prospective study included 85 patients newly diagnosed with in situ or invasive breast cancer eligible for BCS. Their degree of depression/anxiety and attitude toward the decision-making process were measured using the Hospital Anxiety and Depression Scale (HADS) and Control Preference Scale (CPS), respectively. After receiving information on both surgical methods, the patients indicated their preferred surgical method and completed the CPS at their initial and second visits before surgery. RESULTS: After the diagnosis of breast cancer, 75.3% of patients showed abnormal or borderline HADS scores for depression and 41.2% for anxiety. Patients with borderline or abnormal degrees of depression were more likely to have coexisting abnormal degrees of anxiety (p < 0.001). However, the presence of depression or anxiety was not associated with patients' surgical choices (p=0.394 and 0.530, respectively). Patients who preferred a more active role in the decision-making process were more likely to choose mastectomy over BCS, while those who were passive or collaborative chose BCS more frequently (p=0.001). CONCLUSION: Although many patients with newly diagnosed breast cancer experience depression and anxiety before surgery, these do not affect the choice of surgical method; however, their attitudes toward the decision-making process do.